Midlatitude Plasma Blob‐like Structures Along With Super Equatorial Plasma Bubbles During the May 2024 Great Geomagnetic Storm - Wenjie Sun; Guozhu Li; Biqiang Zhao; Shun‐Rong Zhang; Yuichi Otsuka; Lianhuan Hu; Guofeng Dai; Xiukuan Zhao; Haiyong Xie; Yi Li; Jianfei Liu; Yu Li; et al. (Geophysical Research Letters)
Abstract Plasma blob is generally a low‐latitude phenomenon occurring at the poleward edge of equatorial plasma bubble (EPB) during post‐sunset periods. Here we report a case of midlatitude ionospheric plasma blob‐like structures occurring along with super EPBs over East Asia around sunrise during the May 2024 great geomagnetic storm. Interestingly, the blob‐like structures appeared at both the poleward and westward edges of EPBs, reached up to 40°N magnetic latitudes, and migrated westward several thousand kilometers together with the bubble. The total electron content (TEC) inside the blob‐like structures was enhanced by ∼50 TEC units relative to the ambient ionosphere. The blob‐like structure at the EPB poleward edge could be partly linked with field‐aligned plasma accumulation due to poleward development of bubble. For the blob‐like structure at the EPB west side, one possible mechanism is that it was formed and enhanced accompanying the bubble evolution and westward drift.